Durability properties of sustainable concrete containing high volume palm oil waste materials - Ul Islam, M.M.; Mo, Kim Hung; Alengaram, Ubagaram Johnson; Jumaat, Mohd Zamin (Elsevier, 2016)
Huge amount of palm oil wastes were produced annually in Malaysia, among these are oil palm shell (OPS) waste and palm oil fuel ash (POFA). OPS is a waste obtained after the palm oil extraction process while POFA is a resulting waste from the incineration process of OPS along with other palm oil wastes such as palm oil fibre and empty fruit bunch. Considering that the combined amount of OPS and POFA waste amounts to about 15 mil t a year, introduction of these materials into concrete could greatly alleviate this issue while at the same time reduces dependency on conventional concrete-making materials. In this paper, the durability properties of a sustainable concrete incorporating high volume palm oil waste materials, namely OPS and POFA were investigated. The concrete comprised of OPS as complete coarse aggregate substitute and POFA as cement replacement material by up to 70%. Although early age strength of the OPS concrete containing POFA was low, the compressive strength of the concrete containing up to 30% POFA was found to be comparable as the control at later stages. Results revealed that although the sorption properties of OPS concrete were increased in the presence of POFA, other durability properties of the concrete such as sulfate resistance, chloride ion permeability and drying shrinkage were improved at various replacement levels of POFA. For instance, the increase of POFA by up to 50% gave improved sulfate resistance of the OPS concrete and the best performance was found at 30% POFA. In the case of chloride ion permeability and drying shrinkage properties, while the use of up to 50% POFA did not improve the performance of the OPS concrete with water-to-binder ratio of 0.3, the incorporation of 70% POFA in the OPS concrete with water-to-binder ratio of 0.4 exhibited improved behavior compared to the corresponding control concrete.